Study into impacts of formation sands on foam performance during drainage gas production—Take Qinghai Oilfield’s Sebei Gasfield for example - Li, Nan; Jiang, Weidong; Jiang, Yixin; Yang, Jinmin; Cao, Guangqiang; Zheng, Rui; Feng, Daqiang; Wang, Haoyu; Xu, Zhiyu; Peng, Bin; Li, Furong; Kang, Ruixin; et al. (Frontiers in Earth Science, 2023)
Foam drainage gas production is a gas production technology for low-pressure gas well in domestic and abroad industries. In Qinghai Oilfield's Sebei Gasfield, sand inflow often occurs during drainage production. In order to reveal the impacts of formation sands on drainage gas production, a lab test was conducted to make a study on foam performances of different foam drainage agents in case of sand inflow. A laboratory test was employed to study the foam performances of different foaming agents under varies scenes of sand inflow, to reveal the impacts of formation sands during foam drainage gas recovery. In this study, four foaming agents, i.e., OP-10, Sodium dodecyl benzene sulfonate, Hexadecyl Trimethyl Ammonium Bromide(CTAB), and Lauramidopropyl Hydroxy Sulfobetaine, were selected to compare with the field compound foam drainage agent QH-X1. Following patterns can be revealed by macroscopic and microscopic experimental results: Foam formed by an ionic-type foam drainage agent is more stable when the hydrophilic sand particles are smaller ( which means they have larger specific surface areas and the adsorption energy levels between the sand and bubbles are higher); while foam formed by non-ionic foam drainage agent OP-10 has a short stable period because its polarity is weaker than that of ionic-type agent foam and the adsorbability of the foam on the hydrophilic particles is weak; under different sand conditions, the impacts of different foaming agent types on the average bubble area, bubble wall thickness, and Plateau Boundary are markedly different, and appear decreasing tendency with anionic foaming agents, is the trend can be more obvious when the sand particles are coarser. The study on QH-X1 shows that the foam parameters are generally lower as the sand particles are smaller, but the changing trends can be different after sand is involved. Particles constitute an adsorption film at the gas-liquid interface and a laminar structure within each interbubble thin liquid film, thus improving bubble coalescence and unloading stability. So, the inflow of the hydrophilic sands increases the stiffness, half-life period, and comprehensive rate of the QH-X1-induced foam.